ANALISIS KESESUAIAN PERAIRAN UNTUK BUDIDAYA IKAN KERAPU MACAN (Epinephelus fuscoguttatu) DI PERAIRAN PULAU TEGAL KECAMATAN TELUK PANDAN KABUPATEN PESAWARAN - Glenn Valentino; Abdullah Aman Damai; Herman Yulianto (e-Jurnal Rekayasa dan Teknologi Budidaya Perairan, 2018)
Tiger grouper is a marine aquaculture commodities that has good prospects to be developed. One of the areas that could potentially be used as a place of tiger grouper fish farming is the Tegal Island, Pesawaran. The purpose of this research was to analyze the level of water quality for fish farming tiger grouper (Epinephelus fuscoguttatus). This research was carried out in March-May 2017 descriptive analytic nature by doing the observations on the quality of waters which include physical and chemical parameters. The data that used in this research sourced from primary data about the suitability waters of the island while the secondary data is form in research location maps. There were 4 sampling stations which determined with global positioning system (GPS). The results showed that the water quality which is owned by the island's waters on station 1, 2, 3 and 4 were in the quite appropriate category for the cultivation of tiger grouper.